2013
DOI: 10.1097/mph.0b013e31827e91bc
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity From Arsenic Trioxide for Pediatric Acute Promyelocytic Leukemia

Abstract: The aim of this study was to investigate the hepatotoxicity induced by arsenic trioxide (As2O3) at a therapeutic dose for pediatric acute promyelocytic leukemia (APL). A total of APL patients received As2O3 treatment by IV drip. Hepatotoxicity was monitored based on the observations of the dynamic changes in liver function and treatment responses. The influencing factors of hepatotoxicity were further analyzed. Liver impairment occurred in 24.4% of the patients, most of which was mild and moderate in severity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Moreover, these experiments demonstrate that iAs toxicity during chronic exposure is largely due to effects sustained during the latter part of the exposure. These data are consistent with findings in humans and other animal models showing that iAs is a hepatotoxicant [14,22,[34][35][36] and suggest that hepatic toxicity is responsible for lethality in this system, regardless if larvae are reared in egg water or embryo medium.…”
Section: Ias Toxicity In Zebrafish Embryos Is Enhanced Following Livesupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, these experiments demonstrate that iAs toxicity during chronic exposure is largely due to effects sustained during the latter part of the exposure. These data are consistent with findings in humans and other animal models showing that iAs is a hepatotoxicant [14,22,[34][35][36] and suggest that hepatic toxicity is responsible for lethality in this system, regardless if larvae are reared in egg water or embryo medium.…”
Section: Ias Toxicity In Zebrafish Embryos Is Enhanced Following Livesupporting
confidence: 91%
“…Strong data from epidemiological and animal studies have shown that exposure to high levels of arsenic are associated with diabetes, liver disease, cardiovascular disease, cancer, and premature death, and acute to high levels are lethal [11][12][13]. Hepatocytes are among the most severely affected cells, as the liver is the site where majority of iAs is metabolized [14][15][16][17][18][19][20][21][22][23]. Indeed, we found that one stress response pathway, the unfolded protein response (UPR), was activated after chronic (6-120 hpf) iAs exposure in the liver of zebrafish larvae [9].…”
Section: Introductionmentioning
confidence: 99%
“…As 2 O 3 is currently used as a first-line chemotherapeutic drug for APL because it can effectively induce apoptosis in leukemia cells [Zhang et al, 2001]. However, the clinical application of the agent is limited by its side effects that include hepatotoxicity [Hao et al, 2013], cardiotoxicity [Barbey et al, 2003], and nephrotoxicity [Vuky et al, 2002], as well as sudden death [Westervelt et al, 2001]. The adverse effects of As 2 O 3 are usually caused by its cytoand genotoxic effects that are mediated by oxidative stress in normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, in most phase II clinical trials, the curative benefit of ATO against solid tumors is much less effective than that against APL because its dosage required to exert anticancer effect is higher than those required in hematologic malignancies (Lin et al, 2007;Liu et al, 2013). High doses of ATO are prone to cause severe toxic effects, including hepatotoxicity, cardiotoxicity, nephrotoxicity, and even sudden death (Hao et al, 2013;Vineetha et al, 2014). Therefore, dose-dependent toxicity and drug resistance considerably restrict ATO application for treatment of solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…ious anti-cancer drugs (Curtin and Szabo, 2013;Hao et al, 2013). Apoptosis is a complex process mainly regulated by the Bcl-2 family of anti-and pro-apoptotic proteins, such as Bcl-2 and Bax, respectively.…”
Section: An Inhibited the Activation Of Nf-κb Downstream Effectors Imentioning
confidence: 99%